Laparoscopic treatment of annular pancreas in a neonate - Dr Ayushi Vig; Dr Kirtikumar J Rathod; Dr Neeraj Gupta; Dr Kamlesh Kumari; Dr Arvind Sinha (Elsevier, 2021)
Introduction: Duodenal obstruction due to annular pancreas is a rare entity. Among the causes of neonatal obstruction described by Robert Gross, annular pancreas comprises less than 1% of total group (Gross and Chisholm, 1944) [1]. Herewith, we present a case of annular pancreas causing duodenal obstruction in a neonate for which we performed laparoscopic duodeno-jejunostomy and placed a trans anastomotic naso-jejunal feeding tube. Technique description: A 2-day old neonate presented with complaints of bilious vomiting since birth. Clinical findings and radiological imaging were suggestive of duodenal obstruction. The patient was planned for diagnostic laparoscopy. Intraoperatively, a large annular pancreas was noted to obstruct the second part of duodenum. Duodeno-jejunal anastomosis was performed using polydioxanone 5-0 in a single layer. After completion of the posterior layer, a 6Fr infant feeding tube was placed trans anastomotic reaching mid jejunum. The patient tolerated the procedure well and feeds were started on POD 2 via the naso-jejunal trans-anastomotic tube. Conclusion: Laparoscopic duodeno-jejunostomy with the placement of a trans-anastomotic tube is beneficial for the patient as feeds can be started within 48 hours or even earlier. Moreover, laparoscopic approach increases precision in dissection due to greater magnification, decreases overall morbidity and improves cosmesis. Laparoscopic duodeno-jejunostomy, though technically challenging, is feasible in the neonatal age group.